2007
DOI: 10.1089/ars.2007.1665
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Raft–Mediated Uptake of Cysteine-Modified Thioredoxin-1: Apoptosis Enhancement by Inhibiting the Endogenous Thioredoxin-1

Abstract: Thioredoxin-1 (TRX) plays important roles in cellular signaling by controlling the redox state of cysteine residues in target proteins. TRX is released in response to oxidative stress and shows various biologic functions from the extracellular environment. However, the mechanism by which extracellular TRX transduces the signal into the cells remains unclear. Here we report that the cysteine modification at the active site of TRX promotes the internalization of TRX into the cells. TRX-C35S, in which the cystein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…We infer that yeast TRX affects the gastric cells mainly from the extracellular side in this study. In the previous report, recombinant human TRX was observed to enter into ATL2 cells gradually over 24 h. [30][31][32] We show that yeast TRX is digested within only several hours (Fig. 1), and thus it is unlikely that large fraction of active yeast TRX without denaturation enters the gastric cells.…”
Section: Discussionsupporting
confidence: 60%
“…We infer that yeast TRX affects the gastric cells mainly from the extracellular side in this study. In the previous report, recombinant human TRX was observed to enter into ATL2 cells gradually over 24 h. [30][31][32] We show that yeast TRX is digested within only several hours (Fig. 1), and thus it is unlikely that large fraction of active yeast TRX without denaturation enters the gastric cells.…”
Section: Discussionsupporting
confidence: 60%
“…In particular, a TRX mutant, TRX-C35S (with replacement of cysteine 35 by serine), was found to bind rapidly to the cell surface and be internalized into the cells through LRs in the plasma membrane. This indicates that the cysteine at the active site of TRX is important for the internalization and signal transduction of extracellular TRX through LRs (156,210).…”
Section: Thioredoxinmentioning
confidence: 98%
“…These results strongly suggested that formation of disulfide bond between MIF and cell surface TRX is involved in the internalization of MIF. Previously, we reported that TRX-C35S bound to ATL-2 cells much effectively than TRX-WT (20). There is evidence that a disulfide bond is involved in the binding of TRX-C35S to cell surface molecules.…”
Section: Discussionmentioning
confidence: 93%
“…Since endogenous TRX is expressed on the surface of ATL-2 cells and endothelial cells (10,20,24), we assumed that cell surface TRX is involved in the internalization process of MIF into the cells. We assessed the expression of TRX on the surface of ATL-2 cells or Jurkat T cells by flow cytometry.…”
Section: Mif Internalized Into Cytosol Of Atl-2 Cellsmentioning
confidence: 99%